Effects of dietary polyphenols from agricultural by-products on mucosal and humoral immune and antioxidant responses of convict cichlid (Amatitlania nigrofasciata) - Seyed Hossein Hoseinifar (2020)
© 2019 Elsevier B.V. In the present study, the effects of dietary supplementation with polyphenols extracted from agricultural by-products were investigated on serum and/or skin mucus antioxidant and immune responses, and hematological parameters of the convict cichlid (Amatitlania nigrofasciata). Polyphenols extracted from chestnut wood (CW) and olive mill waste water (OMWW) were provided as a mixture (PMIX) (9:1, CW:OMWW). PMIX concentrations of 0.5, 1.0 and 2.0 g/kg of diet were employed. Fish were stocked in 12 tanks and fed with the enriched diets for 8 weeks. After the 8-week period, serum total protein, lysozyme, total immunoglobulins (Ig), catalase (CAT) and radical scavengering activity (RS), skin mucus total protein, total Ig and peroxidase activity, and blood hematological parameters were determined. The results showed that, regardless of inclusion level, skin mucus total Ig and lysozyme activity were significantly increased in the PMIX-treated fish compared to control. The most pronounced changes were related to the supplementation with 2.0 g/kg of PMIX. Similar results were noticed in cases of serum total protein and total Ig. Serum RS and peroxidase activity the fish receiving the 2.0 g/kg PMIX treatment were significantly higher than the other treatments. However, there were no significant differences in the activities among the other treated groups. Serum CAT activity of the fish in the 2.0 g/kg PMIX treatment was significantly higher than the other treatments. Serum CAT activity of the fish in 1.0 g/kg PMIX was significantly higher than the control group, but there were no significant differences in the serum CAT activity between the control and 0.5 g/kg PMIX treatments. There were no significant difference in blood RBC, hematocrit and MCV values among the treatments. In conclusion, PMIX at 2.0 g/kg markedly improves humoral and mucosal immune responses and serum antioxidant responses of the convict cichlid, effects that are probably related to the antioxidant and health-promoting nature of PMIX. Therefore, 2.0 g/kg PMIX is recommended as dietary inclusion levels to increase the overall health of convict cichlid.